(untitled) (Bioresearch Communications, 2024)
Bangladesh is well known for the abundant range of fish. Though fish consumption and variety are very high in Bangladesh, the biodiversity has been alarmingly declining in recent years due to a number of factors including the country’s rapid population growth, industrial water pollution, natural disasters, sea intrusion, salinity, overexploitation of fisheries, use of harmful gear, and dewatering of waterbodies. Given that 60% of Bangladesh’s rural poor are functionally landless, lack of access to land and water for agricultural production, and rely, in part, on shared resources like fish for their livelihoods and food, the loss of fish biodiversity could pose a special challenge for them. Considering all of this, biofloc technology ensures safe food and higher productivity in high-density fish farming in a limited area by being sustainable and ageless. In order to satisfy the demands, more creative and effective techniques for growing and harvesting fish have been created as the fishing business has developed. Present study analyses the fatty acid profile of two commonly consumed fish species Oreochromis niloticus (Tilapia) and Systomus sarana (Shorputi). These fishes were farmed in biofloc system. They were fed commercial feeds and organic feed. Later the the fatty acid profile of both groups were measured. The organic feed group showed higher level of PUFA, omega 3 & 6 fatty acid. Through biofloc technology it is possible to produce fish species with high nutritional level using minimum land and water resources. Sustainable food system can be developed through more research in Bangladesh. Bioresearch Commu. 10(2): 1592-1596, 2024 (July)